2002
DOI: 10.1109/tsa.2002.804541
|View full text |Cite
|
Sign up to set email alerts
|

A robust high accuracy speech recognition system for mobile applications

Abstract: This paper describes a robust, accurate, efficient, low-resource, medium-vocabulary, grammar-based speech recognition system using Hidden Markov Models for mobile applications. Among the issues and techniques we explore are improving robustness and efficiency of the front-end, using multiple microphones for removing extraneous signals from speech via a new multi-channel CDCN technique, reducing computation via silence detection, applying the Bayesian information criterion (bic) to build smaller and better acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In addition to their use in voice calls, researchers have recently tried to develop different applications based upon the sensing capabilities of a mobile phone's microphone. A very successful example is that of speech recognition systems [Deligne et al, 2002], which are widely implemented in current mobile phones. These systems enable users to operate the mobile phone by means of voice command without a keyboard.…”
Section: Microphonementioning
confidence: 99%
“…In addition to their use in voice calls, researchers have recently tried to develop different applications based upon the sensing capabilities of a mobile phone's microphone. A very successful example is that of speech recognition systems [Deligne et al, 2002], which are widely implemented in current mobile phones. These systems enable users to operate the mobile phone by means of voice command without a keyboard.…”
Section: Microphonementioning
confidence: 99%
“…However, studies (Zhang et al, 2000) have shown that low-bandwidth connections to the server can result in significant degradation of speech recognition quality. In contrast, local speech recognition (Deligne et al;Varga et al, 2002) on the mobile device eliminates the need for high-speed communication. Local speech recognition limits the kinds of mobile devices that are powerful enough to perform speech processing; however, the computing power of mobile devices is increasing.…”
Section: Related Workmentioning
confidence: 99%
“…Lowering the number of Gaussians to reduce the CPU cost is effective up to a certain degree. If the observation model is less accurate, the search the number of Gaussian components to each state (Deligne et al 2002). The objecThe theoretical upper limit on the number of Gaussian components is given by during the model building only if they significantly contribute to the likelihood increase.…”
Section: Model Organizationmentioning
confidence: 99%